Diagnóstico de anaplasmosis bovina por los métodos de Giemsa y Elisa indirecto y su relación con los valores sanguíneos, en la provincia de Zamora Chinchipe - Torres Quille, Luis Eduardo (2015)
61 samples of blood were analyzed, taken from asymptomatic cattle in four sectors: North, South, East and West from the province of Zamora Chinchipe, using two types of vacunatainer tubes with anticoagulant and without coagulant. The diagnosis was released by blood smear which are stained with Giemsa a “staining reagent for bovine blood plates”, and the immunoassay technique iELISA (ELISA indirectly) comparing these results with the blood values through the hemoglobin with the QBC technology “a technique of blood analysis”. The general prevalence of bovine anaplasmosis a sample that through the staining of Giemsa is about 56% corresponding to the South side 73% for the North side, a 69%, the East side 83% and the West side with a 13%; the animals that are less than 1year old are affected with a 77%; being the prevalence of a 56%foro both sexes; and according to their breeds an 83%, for the mixed race ones a 55%, for the Holstein 50%, for the Jersey 44% and for the Brown Swiss. By the immunoassay technique (iELISA) we have the general prevalence of anaplasmosis is of 98%, with the prevalence’s on the South, East and West sides of a 100%. Referring to the sex, the males present a prevalence of 100% and the females of 98%, the Brown Swiss, Jersey and Mixed races present a higher prevalence of a 100% and the Holstein a 98%. Within the hematological disorders we found that an 85% of samples are normal for the Hematocrit, 89% are normal for the Hemoglobin, 52% are normal for the White Series, 90% are normal for the Eosinophil’s, 30% are normal for the lymphocytes and monocytes and 30% normal for platelets, showing that the alterations disagree with the Giemsa results or with the positive cases, which determinates that these animals have already progressed with the disease or they are asymptomatic carriers. The 90% of farmers that were surveyed say that they have presence the disease being summer the season with a higher presence, all of them know the symptoms. The factors associated with the presence of Anaplasmosis bovine, we can take note of the feeding systems, the presence of ticks and other mechanic vectors including the own livestock.